A Multiuser Detection Algorithm in the Uplink SC-FDMA System for Green Communication Network - Peng Bao; Qingyang Guan; Mingxiang Guan (IEEE Access)
The Single-carrier Frequency-Division Multiple Access (SC-FDMA) communication scheme is the key technique in green communications and networking for 5G for the uplink of SC-FDMA multiuser systems due to frequency differences introducing access interference. The precision of the traditional parallel and serial interference cancellation algorithms is not high, and the number of required iterations for achieving satisfactory results is large. A new algorithm for the optimal weighted parallel interference cancellation (PIC) is proposed to eliminate the multiple access interference. This method has higher precision than the traditional PIC and the number of interference elimination iterations required is low.